Get set for study abroad - Barron, Tom, Dr (Get set for university., 2006)
Get Set for Study Abroad is a guide-book for students who are thinking of studying outside the UK as part of their home degree and for others who want to know what is involved. It takes you through the whole process, from finding out about the opportunities available and making your selection of a programme up to completing the studies and returning home. It explains what things you need to think about at each stage as you make your preparations and then carry out your studies. There are sections on academic requirements, costs and funding. The book also offers advice on study skills and outlines issues which arise in intercultural communication. It gives particular coverage of programmes in the European Union (such as Erasmus/Socrates) and the USA, the two main areas of interest for UK students. Though the focus is largely on undergraduates, there are sections dealing also with postgraduate study. Student commentaries, a guide to web-sites and printed materials, and a glossary of the terms you are most likely to encounter are also included. The text cuts through the red-tape and bureaucratic language of much of the programme literature and presents a student-friendly viewpoint with candour and good humour.--